Effect of Tilt Angle on Solar Cell Efficiency and Electrical Energy of Nanofluid Filled Photovoltaic-Termal (PV/T) Systems - Ananda, Fadilla; Jelita, Marhama (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
This study aims to analyze the effect of nanofluid concentration and panel tilt angle variation on photovoltaic-thermal (PV/T) system efficiency using numerical simulation with the Finite Element Method (FEM). The results showed that the optimal nanofluid concentration of 20% resulted in an even distribution of fluid flow, while increasing the concentration to 20% at an inclination angle of Ï€/6 decreased the PV cell temperature, increased the photovoltaic efficiency to 12.04%, and the best electrical power of 36.71 W. The highest thermal efficiency of 69.5% was achieved at a concentration of 20% with an inclination angle of Ï€/6, while the highest total efficiency of 81.7% was achieved at an inclination angle of Ï€/3. The optimal combination of nanofluid concentration and tilt angle was shown to significantly improve the energy efficiency of the PV/T system, making an important contribution to the development of more efficient renewable energy technologies.